2009
DOI: 10.1038/sj.bjc.6605192
|View full text |Cite
|
Sign up to set email alerts
|

Dexrazoxane-afforded protection against chronic anthracycline cardiotoxicity in vivo: effective rescue of cardiomyocytes from apoptotic cell death

Abstract: Background: Dexrazoxane (DEX, ICRF-187) is the only clinically approved cardioprotectant against anthracycline cardiotoxicity. It has been traditionally postulated to undergo hydrolysis to iron-chelating agent ADR-925 and to prevent anthracycline-induced oxidative stress, progressive cardiomyocyte degeneration and subsequent non-programmed cell death. However, the additional capability of DEX to protect cardiomyocytes from apoptosis has remained unsubstantiated under clinically relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 50 publications
2
43
0
Order By: Relevance
“…However, the DEX/ ANT ratio and dosing interval could have been suboptimal in this study. It has been also demonstrated that DEX pretreatment (20:1) is able to very effectively prevent the onset of both degenerative changes and apoptotic cell death induced by chronic ANT treatment in rabbits (DAU 3 mg/kg, weekly for 10 weeks) (208). DEX treatment rescued cardiomyocytes from complex proapoptotic signaling, and resulting cell death and parameters of apoptosis correlated well with the cardiotoxicity parameters.…”
Section: Cardioprotection Against Ant Cardiotoxicity In Vivomentioning
confidence: 82%
See 2 more Smart Citations
“…However, the DEX/ ANT ratio and dosing interval could have been suboptimal in this study. It has been also demonstrated that DEX pretreatment (20:1) is able to very effectively prevent the onset of both degenerative changes and apoptotic cell death induced by chronic ANT treatment in rabbits (DAU 3 mg/kg, weekly for 10 weeks) (208). DEX treatment rescued cardiomyocytes from complex proapoptotic signaling, and resulting cell death and parameters of apoptosis correlated well with the cardiotoxicity parameters.…”
Section: Cardioprotection Against Ant Cardiotoxicity In Vivomentioning
confidence: 82%
“…Surprisingly, effective cardioprotection with DEX was not associated with significant decrease of moderately elevated markers of lipoperoxidation. In addition, no correlation has been found between myocardial malondialdehyde levels and parameters of cardiac function (208).…”
Section: Cardioprotection Against Ant Cardiotoxicity In Vivomentioning
confidence: 94%
See 1 more Smart Citation
“…The study was performed by using the previously well established animal model of chronic ANT cardiotoxicity (Š imů nek et al, 2004;Popelová et al, 2009;Š těrba et al, 2011). Adult male Chinchilla rabbits (ϳ4 months old; ϳ3.5 kg; n ϭ 46; Velaz, Koleč u Kladna, Czech Republic) were housed under a 12-h light cycle with constant temperature and humidity and free access to tap water and a standard laboratory pellet diet.…”
Section: Methodsmentioning
confidence: 99%
“…Significant elevation of cTns (both cTnT and cTnI) has been observed in many experimental models of chronic ANT cardiotoxicity [9][10][11] and the majority of data show that they could be an early marker that rises before the deterioration of LV systolic function [12][13][14]. Scattered data in the literature, including our own [15][16][17], has suggested that ANT-induced cardiac damage is associated with a relatively prolonged release of cTns, but further details are lacking.…”
Section: Introductionmentioning
confidence: 90%